EDUKASI KESEHATAN BAGI REMAJA MELALUI PROGRAM GENERASI SEHAT (GENSET) DI KAMPUNG CIBUNGKUL KOTA TASIKMALAYA - Maulana, Restu Fuji Akbar Maulana; Syehar, Nasfa Fitriani; Agustina, Shania; Nandiana, Zulfa; Maulana Firmansyah, Muhammad Rizki; Haidar, Muslim (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Adolescents are an age group in transition to adulthood and are vulnerable to physical and mental health problems. This condition is seen in adolescents in Cibungkul Village, Sukamajukaler Subdistrict, RW 12 and 13 where field observatios indicate allow understanding of adolescent health and future planning. The Healthy Generation Program “GENSET” aims to provide understanding, raise awareness about adolescent health and create physically and mentally healthy adolescent. This program was implemented in Cibungkul Village, Sukamajukaler Subdistrict, involving 26 participants. The community service activity method Participatory Action Research (PAR) combines educational approaches, socialization, and free health service. The results of the activity showed an increase in participant participation in the activity, participant enthusiasm and positive responses during the activity indicate that the educational method is able to improve adolescent health literacy. With the provision of free health checks, it can increase awareness o participants regarding health conditions.